Differentiating False Loss of Resistance from True Loss of Resistance While Performing the Epidural Block with the CompuFlo® Epidural Instrument. (3rd February 2019) - Vaira, Pasquale; Camorcia, Michela; Palladino, Tiziana; Velardo, Matteo; Capogna, Giorgio
Abstract : Background . The occurrence of false losses of resistance may be one of the reasons for inadequate or failed epidural block. A CompuFlo® epidural instrument has been introduced to measure the pressure of human tissues in real time at the orifice of a needle and has been used as a tool to identify the epidural space. The aim of this study was to investigate the sensitivity and the specificity of the ability of CompuFlo® to differentiate the false loss of resistance from the true loss of resistance encountered during the epidural space identification procedure. Method . We performed epidural block with the CompuFlo® epidural instrument in 120 healthy women who requested labor epidural analgesia. The epidural needle was considered to have reached the epidural space when an increase in pressure (accompanied by an increase in the pitch of the audible tone) was followed by a sudden and sustained drop in pressure for more than 5 seconds accompanied by a sudden decrease in the pitch of the audible tone, resulting in the formation of a low and stable pressure plateau. We evaluate the sensitivity, specificity, and positive and negative predictive values of the ability of CompuFlo® recordings to correctly identify the true LOR from the false LOR. Results . The drop in pressure associated with the epidural space identification was significantly greater than that recorded after the false loss of resistance (73% vs 33%) (P = 0.000001 ). The sensitivity was 0.83, and the AUC was 0.82. Discussion. We have confirmed the ability of CompuFlo® to differentiate the false loss of resistance from the true loss of resistance and established its specificity and sensitivity. Conclusion . An easier identification of dubious losses of resistance during the epidural procedure is essential to reduce the number of epidural attempts and/or needle reinsertions with the potential of a reduced risk of accidental dural puncture especially in difficult cases or when the procedure is performed by trainees.